Animate Objects are Detected More Frequently than Inanimate Objects in Inattentional Blindness Tasks Independently of Threat. Issue 2 (2nd April 2016) - Calvillo, Dustin P.; Hawkins, Whitney C.
ABSTRACT: Inattentional blindness occurs when individuals are engaged in an attention-demanding task and fail to detect unexpected objects in their visual field. Two experiments examined whether certain unexpected objects are more easily detected than others. The unexpected objects were animate and threatening (e.g., snake), animate and nonthreatening (e.g., bird), inanimate and threatening (e.g., gun), or inanimate and nonthreatening (e.g., bed). Three hypotheses were tested: the snake detection hypothesis (snakes will be detected more frequently than all other objects), the animate monitoring hypothesis (animate objects will be detected more frequently than inanimate objects), and the threat superiority hypothesis (threatening objects will be detected more frequently than nonthreatening objects). Only the animate monitoring hypothesis was supported in both experiments. These results suggest that animate objects capture attention in the absence of task-relevant goals and that snakes do not show an advantage over other animate objects in inattentional blindness tasks.